2005
DOI: 10.1051/0004-6361:20035742
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a redshifted X-ray emission line in the symbiotic neutron star binary 4U 1700+24

Abstract: Abstract. We present the spectral analysis of an XMM-Newton observation of the X-ray binary 4U 1700+24, performed during an outburst in August 2002. The EPIC-PN spectrum above 1 keV can be modeled by a blackbody plus Comptonization model, as in previous observations. At lower energies, however, we detect a prominent soft excess, which we model with a broad Gaussian centered at ∼0.5 keV. In the high resolution RGS spectrum we detect a single emission line, centered at 19.19

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
26
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 21 publications
8
26
1
Order By: Relevance
“…The SyXB subclass only started gaining some attention from the scientific community in the last decade only; however, X-ray studies of these sources are still quite sporadic, with only a handful of objects having been explored in this spectral window (Masetti et al 2002(Masetti et al , 2007aRea et al 2005;Paul et al 2005;Tiengo et al 2005;Mattana et al 2006;Patel et al 2007;Corbet et al 2008;Marcu et al 2011;González-Galĺan et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SyXB subclass only started gaining some attention from the scientific community in the last decade only; however, X-ray studies of these sources are still quite sporadic, with only a handful of objects having been explored in this spectral window (Masetti et al 2002(Masetti et al , 2007aRea et al 2005;Paul et al 2005;Tiengo et al 2005;Mattana et al 2006;Patel et al 2007;Corbet et al 2008;Marcu et al 2011;González-Galĺan et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…After this study, Tiengo et al (2005) published a paper on the X-ray behaviour of 4U 1700+24: the authors analysed an observation collected with the XMM-Newton satellite in 2002 and found an emission feature at ≈0.5 keV and an emission line at 0.64 keV which was possibly identified as the red-shifted O VIII Ly-α transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its X-ray spectrum is also variable in the long term. A high-resolution X-ray spectroscopy analysis of 4U 1700+24 during a phase of enhanced activity was performed with XMM-Newton by Tiengo et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…By analogy with the symbiotic stars, which are systems composed of an M-type giant and a white dwarf (WD), these LMXBs are sometimes referred to as "symbiotic X-ray binaries". The protoype of this small subclass, the system GX 1+4, is a wellstudied case (e.g., Chakrabarty & Roche 1997); the second member, object 4U 1700+24, is now receiving more attention Appendix is only available in electronic form at http://www.aanda.org (Masetti et al 2002(Masetti et al , 2006aGalloway et al 2002;Tiengo et al 2005).…”
Section: Introductionmentioning
confidence: 99%